Antiproliferative activity and electrochemical oxygen evolution by Ni(ii) complexes of N′-(aroyl)-hydrazine carbodithioates. Issue 40 (27th September 2021) - Chaurasia, R.; Pandey, Shivendra Kumar; Singh, Devesh Kumar; Bharty, M. K.; Ganesan, Vellaichamy; Hira, S. K.; Manna, P. P.; Bharti, A.; Butcher, Ray J.
Abstract : Synthesized Ni(ii ) complexes have remarkable cytotoxic potential against K562 cancer cells and have better electrochemical water oxidation response than RuO2 . Among complexes 1, 2, and 3, complex-2 shows a better water oxidation response. Abstract : The electrochemical water splitting by transition metal complexes is emerging very rapidly. The nickel complexes also play a very vital role in various biological activities. Here, three new ligands H2 mbhce = N ′-(4-methyl-benzoyl), H2 pchce = N ′-(pyridine-carbonyl) and H2 hbhce = N ′-(2-hydroxy-benzoyl) hydrazine carbodithioic acid ethyl ester and their corresponding Ni(ii ) complexes [Ni(Hmbhce)2 (py)2 ] (1 ), [Ni(pchce)( o -phen)2 ]·CH3 OH·H2 O (2 ) and [Ni(hbhce)( o -phen)2 ]·1.75CHCl3 ·H2 O (3 ) have been synthesized and fully characterized by various physicochemical and X-ray crystallography techniques. The photoluminescence study and thermal degradations were also examined. The treatment of K562 cells with the increasing concentrations of the nickel salts, ligands, and complexes 1, 2, and 3 showed dose-dependent cytotoxicity. The cytotoxic activity of ligands reveals that ligand H2 mbhce is more potent in inhibiting the growth of tumor cells in comparison to other ligands H2 pbhce and H2 hbhce. Cytotoxicity assay results indicate that all complexes have remarkable cytotoxic potential in comparison to either nickel salts or the free ligands. Among these complexes, complex 1 has significantly better anti-tumor activity as compared to complexes 2 and 3 . The electrochemical study of complexes 1, 2, and 3 for water oxidation reveals that all the complexes possess admirable electrocatalytic activity towards oxygen evolution reaction (OER) and have lower overpotential (328, 338, and 370 mV, respectively) than many previously reported complexes and RuO2 (390 mV). Among complexes 1, 2, and 3, complex-2 shows a better water oxidation response. Consequently, these complexes have great potential to be utilized in fuel cells. The more reliable electrochemical parameter TOF is also calculated for all three complexes.